In vivo dosimetry in low-voltage IORT breast treatments with XR-RV3 radiochromic film. (January 2021) - Lozares, Sergio; Font, Jose A.; Gandía, Almudena; Campos, Arantxa; Flamarique, Sonia; Ibáñez, Reyes; Villa, David; Alba, Verónica; Jiménez, Sara; Hernández, Mónica; Casamayor, Carmen; Vicente, Isabel; et al.
Graphical abstract: Highlights: Low-energy photon IORT treatments of the breast are increasing in recent years. The best verification of these treatments is to establish an in vivo dosimetry procedure. XR-RV3 radiochromic films are a suitable dosimeter for measuring low energy photons at high doses. An adequate calibration that considers the beam hardening with the distance significantly improves the measurement accuracy. Abstract: Purpose: The objectives of the study were to establish a procedure for in vivo film-based dosimetry for intraoperative radiotherapy (IORT), evaluate the typical doses delivered to organs at risk, and verify the dose prescription. Materials and methods: In vivo dose measurements were studied using XR-RV3 radiochromic films in 30 patients with breast cancer undergoing IORT using the Axxent® device (Xoft Inc.). The stability of the radiochromic films in the energy ranges used was verified by taking measurements at different depths. The stability of the scanner response was tested, and 5 different calibration curves were constructed for different beam qualities. Six pieces of film were placed in each of the 30 patients. All the pieces were correctly sterilized and checked to ensure that the process did not affect the outcome. All calibration and dose measurements were analyzed using the Radiochromic.com software application. Results: The doses were measured for 30 patients. The doses in contact with the applicator (prescription zone) were 19.8 ± 0.9 Gy. In the skin areas, the doses were as follows: 1–2 cm from the applicator, 1.86 ± 0.77 Gy; 2–5 cm, 0.73 ± 0.14 Gy; and greater than 5 cm, 0.28 ± 0.17 Gy. The dose delivered to the pectoral muscle (tungsten shielding disc) was 0.51 ± 0.27 Gy. Conclusions: The study demonstrated the viability of XR-RV3 films for in vivo dose measurement in the dose and energy ranges applied in a complex procedure, such as breast IORT. The doses in organs at risk were far below the tolerances for cases such as those studied.